Social and Cultural Dimensions of Digital Inclusions - Chulilla-Cano, J. L. (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
The state of Internet Adoption Curve in 2011 for the developed countries reveals an apparently optimistic picture: the majority of European and North American populations have adopted main online tools and resources. However, as access of the majority of these populations doesn’t mean universal access, we review some of the main proposals about Digital Divide and the use of EU Digital inclusion perspective in order to focus on the main obstacles for universal access to Internet.
Keywords: cultural and social dimensions of digital divide; digital divide; digital inclusion; internet adoption curve; IJIMAI